Maastricht and the eastern enlargement of the EU - Jürgen Stehn (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1997)
From a pure welfare economic viewpoint, there is no contradiction between a deepening and a widening of the EU. However, the analysis in this paper shows that the factual degree of deepening efforts within the EU by far exceeds the economically optimal one. Above all, the tendency of the Maastricht treaty towards a centralisation of economic competences, the Common Agriculture Policy, and the Common Cohesion Policy raise high barriers for a full membership of Central and Eastern European countries in the EU. Thus, a full accession of the young market economies to the EU will only be possible after substantial institutional reforms have been made within the EU. For a transition period, European integration policy should aim at opening the European Economic Area (EEA) and the European Free Trade Area (EFTA) for Central and Eastern European Countries.
Keywords: F15; H70; 330; Politische Integration; Wirtschaftsunion; Kosten-Nutzen-Analyse; EU-Staaten; Osteuropa; EWR-Staaten